Contraceptive Practice Among the Married Women of Reproductive Age in the Garments Factory (KYAMC Journal, 2013)
Background: Bangladesh is a country having high density of population in the world. Its fertility rate ranges from 4.1 to 5.49 and life expectancy is 66years while the total fertility rate of Asia is 2.2 and life expectancy 70 years. This study was conducted to investigate the pattern of contraceptive practices among the married women of reproductive age in the garments factory. Material and Methods: This descriptive cross sectional survey was carried out among 240 married women of reproductive age from January to June,2012 in the garments factory of Dhaka city . Data were collected on a pre-tested questionnaire by face to face interview. SPSS version 16 was used to analyzed the data. A p-value of 0.05 was considered significant for inference. Results: The mean age of the study population was 29±6.5 years with the mean age at marriage of 17.18±2.7 years. 73(31%) were practicing some methods of contraception, while 167 (69%) were not using it. OCP (Oral Contraceptive Pill) was the commonest method of contraception followed by Condoms 12(5%), Injectable 12(5%), Implant 12(5%) & Tubectomy 6(3%). None was found using IUCD and Traditional method ( withdrawal, rhythm method ) and emergency contraceptive method. The use of contraceptives were more common in grand multipara (p35 years old ladies (p